Landasan Filosofis dalam Pengembangan Teknologi Pendidikan untuk Peningkatan Literasi Digital Peserta Didik - Arie Ekayudhistira Kirana Tejawati; Winaryati; Syalma Faradila Nur; Warman; Dwi Nugroho Hidayanto; Muhammad Amir Masruhim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of philosophical foundations in the development of educational technology on improving students’ digital literacy. A quantitative approach with an explanatory survey design was employed, involving 360 senior high school students in Samarinda. The research instrument consisted of two main variables philosophical foundations of educational technology and digital literacy measured using a 1–5 Likert scale. Simple linear regression was used to determine the effect between variables. The results indicate that students possess a high level of understanding regarding the philosophical dimensions of educational technology, including humanism, constructivism, digital ethics, and educational values. Meanwhile, students’ digital literacy levels were also categorized as good, although slightly lower than their philosophical understanding. Regression analysis revealed a very strong influence of the philosophical foundations on digital literacy, with an R² value of 0.8022 and p < 0.001. These findings highlight that integrating philosophical values into the development and use of educational technology significantly contributes to enhancing students’ digital competencies. Therefore, educational technology requires not only technical proficiency but also an understanding of values, ethics, and meaning to ensure its reflective, critical, and responsible use in digital learning environments.